WEBSITE SEBAGAI SARANA PROMOSI UKM SOPYAN - Indri Ariyanti; Nita Novita; Delta Khairunnisa; Aris Ganiardi (Politeknik Negeri Sriwijaya, 2020)
Sopyan UKM is one of Palembang's craftsmen of Palembang woven fabric cloths / tajung located in the Tuan Kentang area of Palembang which is led by Mr. Sopyan Candra. The internet is a tool used by UKM Sopyan in introducing and promoting its products. Both through the website and social media such as Instagram, line, and WhatsApp. For this reason, counseling needs to be given on how to create a Website and introduce equipment used in the process of making woven woven cloths / tajung to Sopyan Palembang UKM.